Projeto de um gerador com ímãs permanentes e fluxo axial de 50 KW para aplicação em geração eólica distribuída - Linard, Flavio Jose Alexandre (2014)
Today, there is a worldwide trend in the search for new sources of energy with the lowest possible environmental pollution and the minimum hazard for the human health, mainly due to the generation of electricity. In Brazil, according to the information database for electricity generation from Agência Nacional de Energia Elétrica - ANEEL, the energy production through wind power totalizes about 2.788 MW of power in operation now. Additionally, 163 wind farms are under construction and 127 more were allowed by the government for all the Brazilian states. This scenery, favorable to the development of wind energy, leads to several works of research in the area, related to both wind forecast and the new electric machines for wind turbines. Considering such tendency, this dissertation aims to project an electric generator with the power of 50kW, using Neodymium-Iron-Boron permanent magnets, to be exploited in generating electricity from wind energy. The chosen topology for the generator is that of the Torus machine, characterized by being simple and compact as well as by having a high efficiency. The electromagnetic modeling for analysis of the electric field generator is made by employing the commercial software COMSOL Multiphysics®, which uses the Finite Element Method (FEM) to discretize the studied domain.